Environmental Regulation for Transfer of Pollution-Intensive Industries: Evidence From Chinese Provinces - Li, Weiqing; Sun, Huaping; Du, Yunsu; Li, Ziyao; Taghizadeh-Hesary, Farhad (Frontiers in Energy Research, 2020)
How environmental regulations affect the transfer of pollution-intensive industries is the core issue of balanced regional development and pollution reduction in China. This paper analyses the theoretical mechanism of the impact of environmental regulation on industrial transfer based on the distinction between formal environmental regulation and informal environmental regulation. To this aim, the paper selects panel data of 30 provinces in China from 2008 to 2018 and uses the fixed effect econometric model to test the impact of environmental regulation on the transfer of pollution-intensive industries, then uses a threshold regression model to study the threshold characteristics and spatial heterogeneity of environmental regulation on pollution-intensive industrial transfer. The results show a significant inverted U-shaped relationship between formal environmental regulation and the transfer of pollution-intensive industries. The increase of formal environmental regulation intensity affects restraining and then promoting the transfer out of pollution-intensive industries. The promoting effect also shows the characteristics of first increasing and then decreasing, verifying that there are threshold characteristics and spatial heterogeneity. Overall, informal environmental regulation promotes the transfer of pollution-intensive industries and shows the informal regulation’s economic effect. The paper then puts forward the corresponding policy suggestions, including utilizing clean energy-saving technologies in the industrial sector, which is incredibly significant to realize the coordinated development of environmental protection and economy.